Sapaan Kekerabatan pada Guyub Tutur Bahasa Lio - Maria Floriana Serlin (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2021)
Abstract This study aims at describing the kinship greeting in Lio's speech using sociolinguistic theory. The approach used in this study is a qualitative approach. Data collection uses the method of listening, proficient and fishing rod. This means that researchers directly communicate with informants to gather information about kinship greetings in Lio's spoken language. Both of these methods are complemented by interview, note-taking, and documentation techniques. The results showed that in the kinship relationship based on lineage (direct linkage) in Lio's speech in Ende district, there were 16 greeting words, namely Ema, Ine, Babo, Mamo, Eda, No`o, Weta, Nara, Ka`e, Aji, Ana mamo, Ana embu, Ame du`a, Ine du`a, Ame Lo`o and Ine Lo`o. It is stressful that there are 13 kinship greeting words based on the line of marriage in Lio's speech, namely Ema (tu`a), Ine (tu`a), (Ana) tu`a, Ane, Tata / fai eda, No`o, Haki no` o, Weta, Nara, Kae, Aji, Ipa, and Eja.